Frequency of Antineutrophil Cytoplasmic Antibodies (ANCA) in Some Autoimmune Diseases - Falah S. Manhal; Husam M. Abbas (College of Pharmacy University of Baghdad, 2017)
Anti-Neutrophil Cytoplasmic Antibodies (ANCA) are a heterogeneous group of autoantibodies with a broad spectrum of clinically associated diseases. The diagnostic value is established for Proteinase 3 (PR3)-ANCA as well as Myeloperoxidase (MPO)-ANCA. To estimate the frequency of anti-neutrophile cytoplasmic antibodies (ANCA) in sera from a group of Iraqi patients with some autoimmune diseases compared with a healthy control group. Serum samples were collected from one hundred patient, 47 males and 53 females; with age range of 16-70 years; 20 specimens from patients with systemic lupus erythematosus (SLE), 30 from patients with ulcerative colitis (UC), and 50 from patients with rheumatoid arthritis (RA). A group of 40 apparently healthy blood donors was included as controls. ANCA were checked using enzyme-linked immunosorbent assay (ELISA). Positive ANCA was detected in sera of 18 (18%) patients with autoimmune disorders. Anti-PR3 was detected in 6 (12%) patients with RA, and in 4(13.4%) patients with UC. Anti-MPO was detected in 3(6%) patients with RA and in 5(16.6%) patients with UC. All serum samples of patients with SLE showed negative ANCA. There were no ANCAs detected in sera from healthy individuals. Mean of serum anti-PR3 (U/ml) among the studied groups was 2.057 in RA, 2.209 in SLE, and 2.283 in UC, and 1.739 in control group. Statistical analysis revealed that differences in the anti-PR3 between RA, UC and controls were highly significant (P > 0.01), whereas just significant with SLE (P> 0.05). Mean of serum of anti-MPO (U/ml) among the studied groups was 0.711 in RA, 0.695 in SLE, and 1.170 in UC, and 0.652 in control group. Statistical analysis revealed that the differences in the anti-MPO between RA and SLE, controls were non significant (P < 0.05), whereas highly significance with UC (P> 0.01).It was concluded that ANCA markers might play a role in the inflammatory process and they are important factors for the clinical course, and prognosis in the patients with autoimmunity. However, ANCA in autoimmune disorders must be interpreted cautiously with particular attention paid to laboratory technique, the size, age and genetic background of the populations studied. Key words: Rheumatoid Arthritis, Systemic Lupus Erythematosus, Ulcerative Colitis, Anti-neutrophile Cytoplasmic Antibodies (ANCA).